The origins of World War One. - Parkinson, Roger (Putnams : New York, 1970)
Presents the diplomatic, military, and political origins of World War I. Includes extracts from contemporary documents.
Bibliography: p. 119.
Keywords: World War, 1914 -- 1918 -- Causes -- Juvenile literature